Estrogen Reverses HDAC Inhibitor-Mediated Repression of Aicda and Class-Switching in Antibody and Autoantibody Responses by Downregulation of miR-26a - Casali, Paolo; Shen, Tian; Xu, Yijiang; Qiu, Zhifang; Chupp, Daniel P.; Im, John; Xu, Zhenming; Zan, Hong (Frontiers in Immunology, 2020)
Estrogen contributes to females’ strong antibody response to microbial vaccines and proneness to autoimmunity, particularly antibody-mediated systemic autoimmunity, in females. We have hypothesized that this is due to estrogen-mediated potentiation of class switch DNA recombination (CSR) and somatic hypermutation (SHM). As we have shown, estrogen boosts AID expression, which is critical for both CSR and SHM, through upregulation of HoxC4, which together with NF-B critically mediates Aicda (AID gene) promoter activation. We contend here that additional regulation of Aicda expression by estrogen occurs through epigenetic mechanisms. As we have shown, histone deacetylase inhibitors (HDIs) short-chain fatty acid (SCFA) butyrate and propionate as well as the pharmacologic HDI valproic acid upregulate miRNAs that silence AID expression, thereby modulating specific antibody responses in C57BL/6 mice and autoantibody responses in lupus-prone MRL/Faslpr/lpr mice. Here, using constitutive knockout Esr1–/– mice and B cells as well as conditional knockout Aicdacre/creEsr1flox/flox mice and B cells, we showed that the HDI-mediated downregulation of Aicda expression as well as the maturation of antibody and autoantibody responses is reversed by estrogen and enhanced by deletion of ER or E2 inhibition. Estrogen’s reversion of HDI-mediated inhibition of Aicda and CSR in antibody and autoantibody responses occurred through downregulation of B cell miR-26a, which, as we showed, targets Aicda mRNA 3’UTR. miR-26a was significantly upregulated by HDIs. Accordingly, enforced expression of miR-26a reduced Aicda expression and CSR, while miR-26a-sponges (competitive inhibitors of miR-26a) increased Aicda expression and CSR. Thus, our findings show that estrogen reverses the HDI-mediated downregulation of AID expression and CSR through selective modulation of miR-26a. They also provide mechanistic insights into the immunomodulatory activity of this hormone and a proof-of-principle for using combined ER inhibitor-HDI as a potential therapeutic approach.